Pengaruh Strategi Pembelajaran Pogil Terhadap Keterampilan Proses Sains Siswa Pada Materi Laju Reaksi Di SMA Negeri 5 Gorontalo - Yahyu Tanaiyo; Lukman Abdul Rauf Laliyo; La Alio; Masrid Pikoli; Akram La Kilo; Hendri Iyabu (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This quantitative study aims to discover the effect of the Process Oriented Guided Inquiry Learning (POGIL) learning strategy on students' science process skills concerning reaction rate material. The study employs a quasi-experimental design with a pre-posttest control group. The instrument used is a multiple-choice test to measure students' science process skills. The sample consists of all students in the XI IPA class at SMA Negeri 5 Gorontalo, totaling 45 students: 22 in the experimental group and 23 in the control group. Data analysis utilizes the Rasch Model and SPSS 16.0 for hypothesis testing using the Wilcoxon test. The analysis results show that the person reliability value is 0.00, indicating weak consistency in answering the questions, while the item reliability value is 0.71, suggesting that the quality of the test items is quite good. The mean difference in item scores from pre-test to post-test is greater in the experimental group (3.83 logit) compared to the control group (1.59 logit). Wilcoxon test results show significant values < 0.05, with the experimental group having a significant value of 0.00 and the control group at 0.00.